6t-13=5t-7

Simple and best practice solution for 6t-13=5t-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6t-13=5t-7 equation:



6t-13=5t-7
We move all terms to the left:
6t-13-(5t-7)=0
We get rid of parentheses
6t-5t+7-13=0
We add all the numbers together, and all the variables
t-6=0
We move all terms containing t to the left, all other terms to the right
t=6

See similar equations:

| 6x^2+18x+36=0 | | -64-8x=0 | | 2(s+1)+4(s+1)+6(s+1)=12(s+1) | | 2/3=1+m | | 7x-11=77 | | v-(-9)=-1 | | 43-(1+4y-2(y+2)=-3(3y-5)-(7(y-1)-10y+8) | | 7+2+15=3x+5x-4x | | 1.5x+41.8=100 | | v-1/2=-7/4 | | -2+3+3a-2=5a+2a-7a+9 | | 1=6x-1 | | -15n=435 | | 3g-5-3g=7g+5-6g | | 22=r+28 | | 43-1(1+4y-2(y+2)=-3(3y-5)-(7(y-1)-10y+8) | | 18b=-198 | | n-9=() | | 4k-1+k=1+3k+10 | | 4w^2–148w=0 | | 7a=52+4 | | -16v=192 | | 11.6+3a=-19.9 | | 4/5a+1/5(a-10)=5+5(a-5) | | 5(3+x)-(8x+9)=4x | | y=52(6)+270 | | 3(x-5)=2x+40 | | 8m=-63 | | 3(x-5)-2(1-x)-3-3(4=x) | | 4y+1=37 | | m-(-29)=8 | | 30k=870 |

Equations solver categories